Coffee and Cigarette Consumption and Perceived Effects in Recovering Alcoholics Participating in Alcoholics Anonymous in Nashville, TN - Reich, Michael S. (2008)
BACKGROUND: Alcoholics Anonymous (AA) members represent an important and relatively understudied population for improving our understanding of alcohol dependence recovery since over one million Americans participate in the program. Further insight into coffee and cigarette use by these individuals is necessary given AA members’ apparent widespread consumption and the recognized health consequences and psychopharmacological actions of these substances. METHODS: Volunteers were sought from all open-AA meetings in Nashville, TN during the summer of 2007 to complete a questionnaire (n=289, completion rate=94.1%) including timeline followback for coffee, cigarette, and alcohol consumption; the Alcoholics Anonymous Affiliation Scale; coffee consumption and effects questions; the Fagerstrom Test for Nicotine Dependence (FTND); and the Smoking Effects Questionnaire. RESULTS: Mean (±SD) age of onset of alcohol consumption was 15.4±4.2 years and mean lifetime alcohol consumption was 1026.0±772.8 kg ethanol. Median declared alcohol abstinence was 2.1 years (range: 0 days–41.1 years) and median lifetime AA attendance was 1000.0 meetings (range: 4–44209 meetings); average AA affiliation score was 7.6±1.5. Most (88.5%) individuals consumed coffee and approximately 33% of coffee consumers drank more than four cups per day (M=3.9±3.9). The most common self-reported reasons for coffee consumption and coffee-associated behavioral changes were related to stimulatory effects. More than half (56.9%) of individuals in AA smoked cigarettes. Of those who smoked, 78.7% consumed at least half a pack of cigarettes per day (M=21.8±12.3). Smokers’ FTND scores were 5.8±2.4; over 60% of smokers were highly or very highly dependent. Reduced negative affect was the most important subjective effect of smoking. CONCLUSIONS: A greater proportion of AA participants drink coffee and smoke cigarettes in larger per capita amounts than observed in general US populations. The effects of these products as described by AA participants suggest significant stimulation and negative affect reduction. Fundamental knowledge of the quantitative and qualitative aspects of coffee and cigarette consumption among AA members will enable future research to discern their impact on alcohol abstinence and recovery.